2023
DOI: 10.1371/journal.pone.0292842
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in mental health and wellbeing among UK students during the COVID-19 pandemic: Clarifying underlying mechanisms

Isla Dougall,
Milica Vasiljevic,
Maja Kutlaca
et al.

Abstract: Universities are seeing growing numbers of students with poor mental health and wellbeing. Given that lower socioeconomic status (SES) students typically have poorer mental health and wellbeing than their peers, this may be, in part, caused by an increase in the number of students attending university from lower SES backgrounds. However, less is known about how socioeconomic inequalities in mental health and wellbeing persist within university communities. Research investigating psychosocial factors that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Other variables related to both burdens and BRFs play a confounding role. Among university students, differences related to sex [6, 8], age or year of study [30][31][32] and income [33,34] have been observed in the levels of perceived burdens and in BRFs. Likewise, adequate social support, de ned as supportive actions by others that facilitate one's ability to cope with a stressful situation [35], may attenuate the burden of stressful events [36,37] and signi cantly buffer the effects of risky behaviour on physical and psychological health [38].…”
Section: Introductionmentioning
confidence: 99%
“…Other variables related to both burdens and BRFs play a confounding role. Among university students, differences related to sex [6, 8], age or year of study [30][31][32] and income [33,34] have been observed in the levels of perceived burdens and in BRFs. Likewise, adequate social support, de ned as supportive actions by others that facilitate one's ability to cope with a stressful situation [35], may attenuate the burden of stressful events [36,37] and signi cantly buffer the effects of risky behaviour on physical and psychological health [38].…”
Section: Introductionmentioning
confidence: 99%